2002
DOI: 10.1016/s0165-0270(01)00532-5
|View full text |Cite
|
Sign up to set email alerts
|

On the use of fast blue, fluoro-gold and diamidino yellow for retrograde tracing after peripheral nerve injury: uptake, fading, dye interactions, and toxicity

Abstract: The usefulness of three retrograde fluorescent dyes for tracing injured peripheral axons was investigated. The rat sciatic was transected bilaterally and the proximal end briefly exposed to either Fast Blue (FB), Fluoro-Gold (FG) or to Diamidino Yellow (DY) on the right side, and to saline on the left side, respectively. The nerves were then resutured and allowed to regenerate.Electrophysiological tests three months later showed similar latencies and amplitudes of evoked muscle and nerve action potentials betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 56 publications
3
53
0
Order By: Relevance
“…However, even though the possibility of "re-uptake" has been suggested previously for FB (Innocenti et al, 1986;Rende et al, 1991;Popratiloff et al, 2001), it has not been demonstrated, and no such information seems to be available for DY. The relatively small number of FG labelled cells as compared to the other tracers, found in our material, could be explained by a less significant re-uptake phenomenon combined with fading, which has previously demonstrated for this tracer (Novikova et al, 1997;Puigdellívol et al, 2002).…”
Section: 6% (Dy)supporting
confidence: 55%
See 3 more Smart Citations
“…However, even though the possibility of "re-uptake" has been suggested previously for FB (Innocenti et al, 1986;Rende et al, 1991;Popratiloff et al, 2001), it has not been demonstrated, and no such information seems to be available for DY. The relatively small number of FG labelled cells as compared to the other tracers, found in our material, could be explained by a less significant re-uptake phenomenon combined with fading, which has previously demonstrated for this tracer (Novikova et al, 1997;Puigdellívol et al, 2002).…”
Section: 6% (Dy)supporting
confidence: 55%
“…However, the reported FG fading (Novikova et al, 1997), for up to a 75% of the previously labelled population after three months of follow-up (Puigdellívol et al, 2002), limits its use as a first tracer. Here, DY would appear to be a better option.…”
Section: 6% (Dy)mentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, ϳ10% of small and medium DRG cells were found positive for the reporter GFP. Puigdellívol-Sánchez et al (46) estimated only 20 -30% of DRG neurons to innervate the hindpaw. Therefore, the relevant transfection efficiency of the present method may exceed 40%.…”
Section: Discussionmentioning
confidence: 99%